Degradation of AB113 using combined photocatalysis and biological processes: Economic choice and enhanced removal of aromatic compounds - Bita Ayati (Biological Environment and Pollution, 2021)
Dyes are important chemical compounds that are applied to textile, paper, food, printing, leather, cosmetics industries, and so on. Textile dyes are aromatic and hardly degradable compounds causing harmful effects such as toxicity, carcinogenesis, and mutagenesis. Conventional treatment processes such as biological process, or adsorption to activated carbon are not very effective for textile wastewater treatment, and therefore advanced treatment process was extended. In this study, decolorization and mineralization of Acid Blue 113 were investigated using combined TiO2/UV-SBR systems. Dye concentration in the effluent of the photocatalytic reactor was selected via the efficiency of dye removal, BOD5/COD ratio, and energy consumption of alkali media. Three hours after applying the samples to the photocatalytic reactor, more than 80% of the dye was removed and the rest was decolorized approximately after passing the bioreactor. Investigation of optimum conditions leads to enhancing the degradation of aromatic compounds. The results show that second-order and Grau are the best models to describe the photocatalytic and biological kinetic data with higher correlation coefficients, respectively.